Software-based methodology for investigating the performance of an adapted model for improving the energy efficiency of induction motor drives - Dinolova Plamena; Ruseva Vyara; Dinolov Ognyan (E3S Web of Conferences)
This paper presents a software-based methodology for evaluating the performance and practical applicability of an adapted theoretical model aimed at improving the energy efficiency of induction motor drives. The methodology includes stages for data acquisition, processing, and analysis using specially developed and existing software tools. Applying the developed tool to an induction motor drive in a metal cutting machine shows an average current of 4.07 A under no-load conditions and 4.44 A under load, with corresponding standard deviations of 0.0253 A and 0.177 A. The results indicate potential annual energy savings of over 5400 kWh by increasing load utilization. The methodology is justified as universal and easily adaptable for various industrial applications, demonstrating a high degree of automation and an analysis tailored for energy managers.